Board of commissioners and corporate governance disclosure in Sharia-compliant companies in Indonesia - Peni Nugraheni; Syed Musa Alhabshi; Romzie Rosman (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
Corporate governance (CG) aims to protect the interests of stakeholders by ensuring that the company is managed properly. This study aims to examine the relationship between board of commissioners (BOC) characteristics and CG disclosure. BOC characteristics consist of board size, board independence, board meeting, educational background, and cross membership. The sample of this study was sharia compliant companies listed in Indonesia’s sharia securities list registered in the year of 2017-2020. The data were analyzed using panel data regression. This study analysis 160 data from 40 companies. The results show that the level of CG disclosure is high reaching 88.89%. It may give a positive value that the companies may already have the awareness to provide adequate disclosure regarding the implementation of CG principles. The results also show that the board independence has positive effect on the CG disclosure. The finding may have impact on the regulator and users to encourage more roles of BOC in CG disclosure.